The art of the word between storytelling and reading during the pandemic - Giuliani, Donella (Opción, 2022)
Since 2020 we experienced hard times, that caught us by surprise. As all the crisis and tragedies that stroke mankind, this one required answer too, and we eventually had to find them, doing the best we could, as modern warriors in times of peace. Art, beauty, and especially literature, came in helphas literature been able to prove its value in the new millennium too? Can it still talk to the hearts of our youngsters? An answer can be provided by the gaze of young readers.